Improving Elementary Students' Knowledge of Clean and Healthy Living Behaviors Through Health Education at Elementary School Students - Muthia Nabilla; Erlinawati Erlinawati (Global Sustainability Research Institute, 2026)
Introduction: Clean and Healthy Living Practices (PHBS) are an essential strategy for improving public health, particularly among elementary school students, who should develop healthy habits from an early age. Limited knowledge and awareness regarding PHBS may increase the risk of health problems in the school environment. This study aimed to evaluate the effectiveness of PHBS health education in improving students’ knowledge and awareness at SD Negeri 005 Langgini, Bangkinang Kota District.Methods: This study employed a pre-experimental one-group pretest–posttest design involving 50 elementary school students from SD Negeri 005 Langgini. The intervention consisted of health education through lectures, discussions, counseling, and practical demonstrations of proper PHBS practices, including correct handwashing techniques. Students’ knowledge was measured using structured pre-test and post-test questionnaires. Data were analyzed descriptively by comparing the percentage of knowledge scores before and after the intervention.Results: The health education program improved students’ knowledge and awareness regarding clean and healthy living practices. The average knowledge score increased from 68% in the pre-test to 85% in the post-test, representing an absolute increase of 17 percentage points (approximately 25% relative improvement). Students actively participated throughout the educational sessions and demonstrated a better understanding of proper handwashing, waste disposal, and maintaining personal and environmental hygiene.Conclusion: PHBS health education effectively improved elementary school students’ knowledge and awareness of clean and healthy living behaviors. The intervention increased the average knowledge score by 17 percentage points, indicating that school-based health education is an effective approach to promoting healthy behaviors among elementary school students.